Relationship between the Mandibular Condyle Position and the Bite Force in the People with Normal Temporomandibular Joint - Hanieh Moghimi; Shahriar Shahab; Zeinab Azizi; Alireza Akbarzade Baghban; Mahdi Niknami; Noureddin Nakhostin Ansari; Ali Kavoosi; Mohammad Ali Moghimi (Hindawi Limited, 2023)
Statement of the Problem. The mandibular condyle position is important in temporomandibular joint (TMJ) disorders. The bite force is a mechanical force that may affect the condylar position. Purpose. To investigate the relationship between condylar position in the glenoid fossa and maximum bite force in adults with normal temporomandibular joint. Materials and Methods. In this cross-sectional study, 23 subjects (21 females and 2 males; mean age 38.88±11.7 years) with 41 joints participated. Right and left joints were examined using cone-beam computed tomography. Maximum bite force was measured using the strain gauge transducer in the regions of right molar, left molar, and incisors. Pearson correlation coefficient, paired sample t-test, and binary logistic regression were employed for analysis. Results. The mean maximum bite force was 169.09 ± 87.7 N. The most common position of the condyle was anterior (n = 36) and inferior (n = 31). The mean of mandibular condyle joint spaces for right and left sides were not statistically significant (P>0.05). There were no relationships between the condylar positions and the mean maximum bite force (P>0.05). Conclusion. The condylar positions in the glenoid fossa are not related to the bite force in the people with normal temporomandibular joint.